What is the prevalence of autism spectrum disorder and ASD traits in psychosis? A systematic review. (April 2017) - Kincaid, Debbie L.; Doris, Michael; Shannon, Ciaran; Mulholland, Ciaran
Abstract: There is increasing evidence to suggest both a symptomatic overlap and a clinically significant degree of co-occurrence between Autism Spectrum Disorders (ASD) and psychotic disorders such as schizophrenia but the nature of such relationships remain unclear. We reviewed the literature reporting prevalence rates of Autistic-like Traits (ALTs) and ASD in populations with a diagnosis of schizophrenia or other psychotic disorder. A search of three large databases was conducted and from this seven studies met the criteria for inclusion. The point prevalence rates for ALTs ranged from 9.6% to 61%, whilst the prevalence rates for diagnosed ASD ranged from <1% to 52% across outpatient and inpatient populations. This suggests that prevalence rates of ALTs and ASD in psychosis populations are much higher than in the general population. This has important implications regarding future research, and clinical implications in terms of ensuring that patients receive the most appropriate diagnosis and treatment. Highlights: Rates of ASD and ASD traits are elevated in a psychosis population. Despite overlaps, there remains a diagnostic distinction between the two disorders. Large-scale epidemiological studies are required to ascertain rates of co-occurrence.